Penerapan Model Pembelajaran Bebrbasis Masalah (Problem Based Learning) untuk Meningkatkan Belajar Siswa pada Mata Pelajaran Fiqih Kelas X di MA Mambaul Ma'arif Denanyar Jombang - Sofia, Siti; Chotimah, Chusnul (MASALIQ, 2025)
This study aims to analyze the implementation of the Problem Based Learning (PBL) model in improving the quality of Fiqh learning for tenth-grade students at MA Mambaul Ma'arif Denanyar Jombang. Using a descriptive qualitative approach, this research collects data through observation, interviews, and documentation. The research results show that the implementation of PBL successfully increased student participation in the learning process, both individually and in groups. This model has proven effective in developing students' critical thinking, analytical, and understanding skills regarding Fiqh concepts relevant to everyday life. Students are also more motivated to learn thanks to the interactive, collaborative, and contextual learning atmosphere. However, several challenges in the implementation of PBL have been identified, such as time constraints, lack of preparation from students and teachers, and the need for adequate supporting resources. To address these issues, an active role of teachers as facilitators, continuous training for teachers, and support facilities from the school are needed. The findings of this research contribute significantly to learning innovations in madrasahs, particularly in preparing students to face academic and real-life challenges. With the more optimal and sustainable implementation of PBL, it is hoped that this model can become an effective learning approach in improving the quality of Fiqh education in madrasah environments. Furthermore, this research can also serve as a foundation for the development of education policies oriented towards competency-based and student creativity-focused learning.